Development of emulsified modified bitumen from industrial waste - Nasreldeen Ishag, Obi Kemony (2023)
Bitumen emulsion is a multi-phase system composed of asphalt, water, and one or more surfactants to stabilise the mixture and it is used for wall coating. Furthermore, the growing volume of global manufacturing waste has resulted in serious environmental issues that necessitate a better waste management strategy. However, the formulation of emulsified modified bitumen from manufacturing waste, such as refined waste oil, could be a viable solution to these issues. The objective of this study is to formulate emulsified modified bitumen (EMB) products, 60/70 grade bitumen were modified with refined waste oil and emulsified with six different emulsifiers (Anionic, Cationic, and Non-Ionic) to be used for surface coating. Samples were formulated by modifying the ratios of bitumen, refined waste oil, and the type of emulsifiers used while keeping other parameters constant. The formulated emulsions were tested and then coated on a drywall substrate, with their performance compared to that of the industrial bitumen emulsion. According to the results, the formulated EMB emulsions had significantly lower emulsion viscosity, good adhesion, and comparable ageing period. More importantly, the heat transfer values (q) in EMB A3 at 60 °C, 45 °C, and 27 °C are 1.80 W, 0.37 W, and 0.41 W respectively. The study also discovered that the higher the bitumen content in cationic EMBs, the greater the ability of the bitumen emulsion for heat insulation. In terms of coating and insulation impact on the substrate, the formulated bitumen emulsion (EMB A3) performs similarly to the industrial bitumen emulsion. More research, however, is required to gain a better understanding of the mechanisms and factors influencing EMB formulation in order to develop an idea for a feasible and environmentally friendly bitumen emulsion.